IESQ Dan Quantum Quotient Terhadap Kinerja Tenaga Pendidik Di MTsN 4 Tulungagung - Rohmiyati, Alin; Prasetyo, Deni Widyo (Otonomi, 2025)
Human Resources occupy the most vital position in schools. It is true that costs are important. So are facilities, infrastructure and technology. However, the availability of these resources is wasted if handled by incompetent people and those who lack commitment. This study aims to: (1) To analyze the influence of IESQ partially on the performance of educators at MTsN 4 Tulungagung. (2) To analyze the influence of Quantum Quotient partially on the performance of educators at MTsN 4 Tulungagung. (3) To analyze the influence of IESQ and Quantum Quotient simultaneously on the performance of educators at MTsN 4 Tulungagung. (4) To analyze the IESQ and Quantum Quotient variables that have a dominant influence on the performance of educators at MTsN 4 Tulungagung. This study uses a quantitative analysis method, namely the analysis of data that has been scored according to the measurement scale that has been determined using statistical formulas. The analysis used is data in the form of numbers. While the quality test uses (1) Descriptive statistical analysis, (2) Verification analysis. (3) Classical assumption test (4) Multiple regression analysis, and (5) Hypothesis testing, (6) Determination Coefficient Analysis (R2). The results of the study indicate that: (1) IESQ partially has a significant influence on the Performance of Educators at MTsN 4 Tulungagung. (2) Quantum Quotient partially has a significant influence on the Performance of Educators at MTsN 4 Tulungagung. (3) IESQ and Quantum Quotient simultaneously have a significant influence on the Performance of Educators at MTsN 4 Tulungagung. (4) Quantum Quotient has the most dominant influence on the Performance of Educators at MTsN 4 Tulungagung.